The Influence of Green Product, Environmental Concern, and Green Trust on Tupperware’s Green Purchase Intention (Study on Ciledug Society) - Widi, Reggy Noviana; Ramli, Yanto (ARE Publisher, 2024)
This study aims to analyze the influence of Green Product, Environmental Concern, and Green Trust on Tupperware’s Green Purchase Intention (Study on Ciledug Society). The population in this study was a community domiciled in Ciledug and the sample used was 135 respondents using the Purposive Sampling method technique. This research uses a type of quantitative research then the analysis method used is Partial Least Square (PLS). The results showed that the variables Green Product and Environmental Concern had a positive and significant effect on Green Purchase Intention, while the Green Trust variable had a positive but not significant effect on Green Purchase Intention.